Andersens drøm: Odin Teatrets forestilling Andersens drøm (2005) - en teaterrejse i frihed og slaveri - Kuhlmann, Annelis (Peripeti, 2024)
Anmeldelse [The issue has been reconstructed from a scanned version of a printed issue, which might result in minor flaws in the text. This is also the cause of the odd page breaks.]